2022
DOI: 10.3389/fped.2022.908226
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between histopathological and intraoperative classifications for pediatric appendicitis and its relationship with the post-operative clinical outcome

Abstract: IntroductionSome studies have shown poor agreement between intraoperative and histopathological classifications for appendicitis, despite their routine use in clinical practice.ObjectiveTo investigate the agreement between histopathological and intraoperative classifications for pediatric appendicitis and evaluate the predictive potential of these classifications for the post-operative outcome.MethodsA retrospective, longitudinal, observational single-center study, carried out with 485 patients up to15 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…However, a pathological examination is considered the gold standard method for diagnosing appendicitis. Additionally, some studies have reported a moderate agreement between intraoperative and histopathological examinations to diagnose appendicitis in children 30–32 . Second, this study spanned a long period, and the timing of surgery and the surgeon's skill level affected the postoperative outcomes.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, a pathological examination is considered the gold standard method for diagnosing appendicitis. Additionally, some studies have reported a moderate agreement between intraoperative and histopathological examinations to diagnose appendicitis in children 30–32 . Second, this study spanned a long period, and the timing of surgery and the surgeon's skill level affected the postoperative outcomes.…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, some studies have reported a moderate agreement between intraoperative and histopathological examinations to diagnose appendicitis in children. 30 , 31 , 32 Second, this study spanned a long period, and the timing of surgery and the surgeon's skill level affected the postoperative outcomes. Additionally, some patients with combined Hirschsprung disease underwent enterostomy simultaneously with appendectomy, which could be confounding for the parenteral nutrition time variable.…”
Section: Discussionmentioning
confidence: 99%